Protecting the Vital Groundwater Sources of Oceanic Islands. Issue 1 (18th January 2022) - Lau, L. Stephen; El‐Kadi, Aly I.; Rong, Kexin; Grobbe, Niels
Key Takeaways: Groundwater contamination following a 1977 chemical spill on the Hawaiian island of Oahu caused alarm and led to swift action in the early 1980s, including closure of several drinking water wells. Legislation and other efforts to remediate and monitor the contamination have been rigorous and nearly continuous. Decades later, a recent study has examined source water protection and economic impact stemming from Oahu's groundwater contamination.